Varus-valgus instability in the anterior cruciate ligament-deficient knee: effect of posterior tibial load - Ohori, Tomoki (J Exp Orthop, 2017)
BACKGROUND: Anterior cruciate ligament (ACL) injury is often accompanied with medial collateral ligament (MCL) injury. Assessment of varus-valgus (V-V) instability in the ACL-deficient knee is crucial for the management of the concomitant ACL-collateral ligaments injury. We evaluated the V-V laxity and investigated the effect of additional posterior tibial load on the laxity in the ACL-deficient knee. Our hypothesis was that the V-V laxity in the ACL-deficient knee was greater than that in the intact knee and attenuated by additional posterior tibial load. METHODS: Eight fresh-frozen porcine knees were used, and a 6°-of-freedom (DOF) robotic system was utilized. A 5 Nm of V-V torque was applied to the intact knee, the ACL-deficient knee, and the ACL-deficient knee with 30 N of constant posterior tibial load, at 30° and 60° of flexion. Then, the 3D path in the intact knee was reproduced on the ACL-deficient knee. The total V-V angle under 5 Nm of V-V torque was assessed and compared among the three statuses. The in situ forces of the ACL under 5 Nm of varus and valgus torques, respectively, were also calculated. RESULTS: The total V-V angle in the ACL-deficient knee under 5 Nm of V-V torque was significantly greater than that in the intact knee, whereas the angle in the ACL-deficient knee with 30 N of posterior tibial load was significantly smaller than that in the ACL-deficient knee and approached that in the intact knee, at both 30° and 60° of flexion. The in situ force of the ACL was approximately 30 N at 30° and 16 N at 60° of flexion under 5 Nm of both varus and valgus torques. CONCLUSIONS: The V-V laxity in the isolated ACL-deficient knee was greater than that in the intact knee. The increased laxity was attenuated and approached that in the intact knee by adding posterior tibial load. Application of posterior tibial load is necessary for accurate assessment of V-V instability in the ACL-deficient knee. Clinically, the V-V laxity in the combined ACL-MCL or ACL-LCL injured knee may be overestimated without posterior tibial load.